THE ROLE OF THE EDUCATOR IN DIRECTING CHILDREN TO CREATIVE ACTIVITY IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Web of Teachers: Inderscience Research, 2024)
This article talks about the role of the educator in directing children to creative activity in preschool educational organizations.